A cable composite material with halogen-free flame retardant functionality and preparation method thereof
The combination of nitrogen-free phosphorus-free co-effect reaction flame retardant with high-density polyethylene with surface modification diatomaceous earth solves the problem of insufficient mechanical strength and flame retardant performance of polyethylene cable materials, and achieves efficient flame retardant effect and Improved mechanical properties.
Patent Information
- Application Number
- CN202411284896.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The mechanical strength of polyethylene cable materials is low and flammable. The amount of existing inorganic flame retardant is high and interface problems lead to reduced mechanical properties and poor flame retardant effect.
Diatomaceous earth modified by the surface of the reactive flame retardant is used as the inorganic modified agent. It forms a nitrogen-phosphorus synergistic reaction flame retardant through ultrasonic dispersion and catalytic reaction, and modify the surface of the diatomaceous earth and combines with high-density polyethylene. Extrusion granulation process forms a cable composite material with good mechanical and flame retardant properties.
It improves the uniform dispersion and interface performance of diatomaceous earth in polyvinyl substrates, enhances the flame retardant performance, forms a long-term flame retardant effect, reduces smoke density and combustion sustainability, and improves the mechanical and flame retardant performance of the material.
Smart Images

Figure CN118772518B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a cable composite material with halogen-free flame retardant functionality and a preparation method thereof. Background Art
[0002] Cables are important carriers for power transmission and signal transmission, and the performance of their materials is directly related to the safety, stability and efficiency of the power system. With the rapid development of the power industry and the continuous improvement of people's safety requirements, the research and application of cable materials are also constantly improving. Polyethylene has many advantages as a cable material, such as good chemical resistance, weather resistance, heat resistance and easy processing and molding. However, due to its own linear structure, the mechanical strength of polyethylene is relatively low, and it is a flammable material itself. Once it burns, it will not only cause huge economic losses, but may also cause serious consequences such as casualties. This actually has a serious limitation on the application of polyethylene in the cable industry. Therefore, how to improve the mechanical strength and flame retardant functionality of polyethylene has become a difficult problem that technicians urgently need to overcome.
[0003] At present, the main way to solve the problem of poor flame retardancy of polymer materials is to add inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide for flame retardant modification. However, this type of inorganic flame retardant actually has poor flame retardant effect and needs to be added in a higher amount. For example, the invention patent with publication number CN105504482A discloses a halogen-free flame retardant linear low-density polyethylene material. By controlling the mass ratio of magnesium hydroxide / aluminum hydroxide, zinc borate and microcapsule red phosphorus, a halogen-free composite flame retardant is compounded to modify polyethylene. However, this method requires too high a flame retardant addition amount, which may cause phase separation due to interface problems in the later stage of use, resulting in a sharp decrease in the mechanical properties of the material. Based on this, the present invention provides a halogen-free flame retardant modified polyethylene composite material, which has good mechanical properties and flame retardant properties and can be directly used in the manufacture of cables. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a cable composite material with halogen-free flame retardant functionality and a preparation method thereof.
[0006] (II) Technical solution
[0007] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 85-95 parts of high-density polyethylene, 5-15 parts of a compatibilizer, 5-10 parts of SBS, 3-6.5 parts of an inorganic modifier, 0.5-1.2 parts of an antioxidant, 0.5-1.5 parts of an ultraviolet absorber, and 1-2 parts of a lubricant;
[0008] The inorganic modified body is diatomaceous earth surface-modified by a reactive flame retardant.
[0009] More preferably, the compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene.
[0010] Further preferably, the preparation method of the inorganic modified body is as follows:
[0011] The acid-treated diatomaceous earth is mixed with toluene, and ultrasonically dispersed for 30-40 minutes at an ultrasonic frequency of 80-120kHz, and then the reactive flame retardant is added to the formed dispersion, and the catalyst is added at the same time, and mechanical mixing is performed, and then the temperature is gradually controlled to 60-70°C. After heat preservation for 3-6 hours, the heating is stopped, and the solid material collected by centrifugal separation is washed and vacuum dried to obtain an inorganic modified body.
[0012] Further preferably, the acid treatment method of the diatomaceous earth is as follows:
[0013] Place the diatomaceous earth in a tube furnace, calcine it at 450-500°C for 1-2h, take it out, cool it naturally, transfer it to dilute sulfuric acid, then control the temperature to 45-55°C, keep it warm for 1-3h under constant stirring, discharge it, wash it and dry it.
[0014] In the above scheme, diatomaceous earth is first treated at high temperature to carbonize organic matter in its pores, and then it is acid-washed to remove impurities in the pores, so that the pore structure of the diatomaceous earth can be fully exposed, and more active reaction sites are exposed at the same time. Then, a catalyst is used to catalyze the amine esterification reaction between the silanol groups on the surface of the diatomaceous earth and the isocyanate groups in the structure of the reactive flame retardant, so that the nitrogen and phosphorus synergistic reactive flame retardant is modified on the surface of the diatomaceous earth to obtain an inorganic modified body.
[0015] Further preferably, the preparation method of the reactive flame retardant is as follows:
[0016] Add 4-isocyanobenzoyl chloride and acetone to a reactor filled with nitrogen, start stirring, and after mixing evenly, add the flame retardant FRC-6 to the reactor under ice bath conditions. After the addition is complete, remove the ice bath, and then add the acidifying agent to the reactor. After the addition is complete, stir at room temperature for 2-4 hours, evaporate to remove the solvent, collect the material, and the reactive flame retardant can be obtained.
[0017] Further preferably, the molar ratio of the 4-isocyanobenzoyl chloride to the flame retardant FRC-6 is 1:2.
[0018] More preferably, the acidifying agent is pyridine or triethylamine.
[0019] More preferably, the catalyst is at least one of dibutyltin diacetate, dibutyltin dilaurate, stannous octoate or dibutyltin didodecylsulfide.
[0020] Further preferably, the antioxidant is a mixture of antioxidant 168 and antioxidant 1010, with a mass ratio of 0.2-0.3:1; the ultraviolet absorber is any one of UV-292, UV-571 or UV-P; and the lubricant is any one of polyethylene wax, zinc stearate or calcium stearate.
[0021] A method for preparing a cable composite material with halogen-free flame retardant functionality comprises the following steps:
[0022] The first step is to weigh each raw material according to the weight and set aside;
[0023] The second step is to add all the raw materials into the mixer, mechanically stir and mix them at a speed of 1000-1500r / min for 30-60min to form a uniform mixture, and then feed the mixture into the extruder through the feeding hopper, control the extrusion temperature to 240-280°C, the screw speed to 200-250r / min, perform the extrusion granulation process, and then pelletize to obtain the cable composite material.
[0024] 3. Beneficial technical effects
[0025] The present invention prepares diatomite with surface modification of nitrogen-phosphorus synergistic reactive flame retardant as an inorganic modified body, and adds it to a high-density polyethylene substrate. First, the presence of the reactive flame retardant is equivalent to forming an organic "transition" layer between the substrate and the diatomite, which greatly improves the interface performance between the substrate and the diatomite, and can promote the diatomite to be evenly dispersed in the substrate system to form a physical cross-linked core. On the one hand, the stress absorption and load transfer function of the diatomite as an inorganic material can be efficiently exerted, and on the other hand, the rich pores exposed by the diatomite can be used to absorb the smoke generated during the combustion process to reduce the smoke density, and the nitrogen-phosphorus synergistic flame retardant can quickly form an expanded carbon layer to protect the substrate and prevent the combustion from continuing, thereby greatly enhancing the flame retardant properties of the polyethylene cable material. In addition, after chemical bonding, the reactive flame retardant is difficult to volatilize and migrate, so it can exist in the substrate for a long time and exert a long-term flame retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0027] Figure 1 This is the infrared analysis test chart of reactive flame retardant. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Example 1
[0029] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 85 parts of high-density polyethylene, 5 parts of maleic anhydride grafted polypropylene, 5 parts of SBS, 3 parts of inorganic modifier, 0.5 parts of antioxidant, 0.5 parts of ultraviolet absorber UV-292, and 1 part of polyethylene wax;
[0030] The preparation method of the cable composite material comprises the following steps:
[0031] The first step is to weigh each raw material according to the weight and set aside;
[0032] In the second step, the raw materials are added into the mixer, and mechanically stirred and mixed for 60 minutes at a speed of 1000r / min to form a uniform mixture, and then the mixture is fed into the extruder through the feeding hopper, and the extrusion temperature is controlled at 280°C and the screw speed is 200r / min. The extrusion granulation process is carried out, and then the cable composite material is obtained through pelletizing.
[0033] The antioxidant is a mixture of antioxidant 168 and antioxidant 1010, with a mass ratio of 0.2:1, and the same applies to the following. Example 2
[0034] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 90 parts of high-density polyethylene, 10 parts of maleic anhydride grafted polyethylene, 8 parts of SBS, 5 parts of inorganic modified body, 1 part of antioxidant, 1 part of ultraviolet absorber UV-571, and 1.5 parts of zinc stearate;
[0035] The preparation method of the cable composite material comprises the following steps:
[0036] The first step is to weigh each raw material according to the weight and set aside;
[0037] In the second step, the raw materials are added into the mixer, and mechanically stirred and mixed at a speed of 1200r / min for 40 minutes to form a uniform mixture, and then the mixture is fed into the extruder through the feeding hopper, and the extrusion temperature is controlled at 260°C and the screw speed is 240r / min. The extrusion granulation process is carried out, and then the cable composite material is obtained through pelletizing. Example 3
[0038] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 95 parts of high-density polyethylene, 15 parts of maleic anhydride grafted polyethylene, 10 parts of SBS, 6.5 parts of inorganic modifier, 1.2 parts of antioxidant, 1.5 parts of ultraviolet absorber UV-P, and 2 parts of calcium stearate;
[0039] The preparation method of the cable composite material comprises the following steps:
[0040] The first step is to weigh each raw material according to the weight and set aside;
[0041] In the second step, the raw materials are added into the mixer, and mechanically stirred and mixed at a speed of 1500r / min for 30 minutes to form a uniform mixture, and then the mixture is fed into the extruder through the feeding hopper, and the extrusion temperature is controlled at 280°C and the screw speed is 250r / min. The extrusion granulation process is carried out, and then the cable composite material is obtained through pelletizing.
[0042] The inorganic modified body in the above embodiment is prepared by the following method:
[0043] S1. Acid treatment of diatomaceous earth
[0044] 5 g of diatomaceous earth was placed in a tube furnace, calcined at 500° C. for 1 h, taken out, cooled naturally, and then transferred to 200 mL of dilute sulfuric acid, and then the temperature was controlled to 50° C., kept warm for 2 h under continuous stirring, discharged, washed and dried to obtain acid-treated diatomaceous earth;
[0045] S2. Preparation of reactive flame retardant
[0046] Add 0.3 g of 4-isocyanobenzoyl chloride and acetone to a reactor filled with nitrogen, start stirring, and after mixing evenly, add 0.84 g of flame retardant FRC-6 to the reactor under ice bath conditions. After the addition is complete, remove the ice bath, and then add 0.03 g of pyridine to the reactor. After the addition is complete, stir at room temperature for 3 hours, evaporate to remove the solvent, and collect the material to obtain a reactive flame retardant;
[0047] The structural formula of the reactive flame retardant is as follows:
[0048] Figure 1 This is the infrared analysis test chart of the reactive flame retardant, where 3000-3100cm -1 The absorption peak at 2800-3000cm is the characteristic absorption peak of CH of benzene ring skeleton. -1 The absorption peaks appearing at 2210-2270cm are the characteristic absorption peaks of CH of methyl and methylene. -1 The absorption peak at 1745 cm is the characteristic absorption peak of the isocyanate group. -1 The absorption peak at 1258 cm is the characteristic absorption peak of C=O of ester group. -1 The absorption peak that appears at is the characteristic absorption peak of P=O.
[0049] S3. Preparation of inorganic modified body
[0050] 2.6 g of acid-treated diatomaceous earth is mixed with toluene, and ultrasonically dispersed for 40 minutes at an ultrasonic frequency of 100 kHz. Then, 1.5 g of a reactive flame retardant is added to the formed dispersion, and 0.1 g of dibutyltin dilaurate is added at the same time. The mixture is mechanically mixed, and the temperature is gradually controlled to 65°C. After heat preservation for 4 hours, the heating is stopped, and the solid material collected by centrifugation is washed and vacuum dried to obtain an inorganic modified body.
[0051] Comparative Example 1
[0052] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 90 parts of high-density polyethylene, 10 parts of maleic anhydride grafted polyethylene, 8 parts of SBS, 5 parts of reactive flame retardant, 1 part of antioxidant, 1 part of ultraviolet absorber UV-571, and 1.5 parts of zinc stearate;
[0053] The preparation method of the cable composite material comprises the following steps:
[0054] The first step is to weigh each raw material according to the weight and set aside;
[0055] In the second step, the raw materials are added into the mixer, and mechanically stirred and mixed at a speed of 1200r / min for 40 minutes to form a uniform mixture, and then the mixture is fed into the extruder through the feeding hopper, and the extrusion temperature is controlled at 260°C and the screw speed is 240r / min. The extrusion granulation process is carried out, and then the cable composite material is obtained through pelletizing.
[0056] Comparative Example 2
[0057] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 90 parts of high-density polyethylene, 10 parts of maleic anhydride grafted polyethylene, 8 parts of SBS, 5 parts of diatomaceous earth, 1 part of antioxidant, 1 part of ultraviolet absorber UV-571, and 1.5 parts of zinc stearate;
[0058] The preparation method of the cable composite material comprises the following steps:
[0059] The first step is to weigh each raw material according to the weight and set aside;
[0060] In the second step, the raw materials are added into the mixer, and mechanically stirred and mixed at a speed of 1200r / min for 40 minutes to form a uniform mixture, and then the mixture is fed into the extruder through the feeding hopper, and the extrusion temperature is controlled at 260°C and the screw speed is 240r / min. The extrusion granulation process is carried out, and then the cable composite material is obtained through pelletizing.
[0061] Comparative Example 3
[0062] A cable composite material with halogen-free flame retardant functionality, comprising the following raw materials in parts by weight: 90 parts of high-density polyethylene, 10 parts of maleic anhydride grafted polyethylene, 8 parts of SBS, 1 part of antioxidant, 1 part of ultraviolet absorber UV-571, and 1.5 parts of zinc stearate;
[0063] The preparation method of the cable composite material comprises the following steps:
[0064] The first step is to weigh each raw material according to the weight and set aside;
[0065] In the second step, the raw materials are added into the mixer, and mechanically stirred and mixed at a speed of 1200r / min for 40 minutes to form a uniform mixture, and then the mixture is fed into the extruder through the feeding hopper, and the extrusion temperature is controlled at 260°C and the screw speed is 240r / min. The extrusion granulation process is carried out, and then the cable composite material is obtained through pelletizing.
[0066] Test Case
[0067] The composite materials in Examples 1 to 3 and Comparative Examples 1 to 3 were made into samples that met the specifications, and various performance tests were performed. The results are recorded in Table 1:
[0068] Table 1 - Performance test results
[0069] Note: The tensile strength test refers to GB / T 1040.2-2006; the limiting oxygen index test refers to GB / T 2406.2-2009, and the test time is 3 months after the sample is placed at room temperature; the total smoke production test sample size is 10cm×10cm×4mm, wrapped in aluminum foil and placed in a cone calorimeter, and the heat flux radiation intensity is controlled to 25Kw / m 2 , the exhaust pipe flow rate is 24L / s, the sample is 25mm high from the radiation cone, and the total smoke production test is carried out.
[0070] According to the test results, the composite materials prepared with inorganic modifiers as additives have good mechanical properties, flame retardant properties, and good smoke suppression effects. After the inorganic modifiers are replaced with diatomaceous earth without surface modification, on the one hand, due to the existence of interface problems, the advantages of diatomaceous earth cannot be effectively exerted, so the mechanical properties are slightly reduced. On the other hand, due to the lack of nitrogen-phosphorus synergistic flame retardants, the overall flame retardant and smoke suppression properties of the material are significantly reduced. After the inorganic modifiers are replaced with reactive flame retardants, the flame retardant properties also show a large decline, probably due to migration and precipitation during storage. After the inorganic modifiers are directly removed, the load transfer effect of diatomaceous earth cannot be utilized, resulting in a significant reduction in both mechanical properties and smoke suppression properties.
[0071] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cable composite material with halogen-free flame retardant functionality, characterized in that: The invention comprises the following raw materials in parts by weight: 85-95 parts of high-density polyethylene, 5-15 parts of a compatibilizer, 5-10 parts of SBS, 3-6.5 parts of an inorganic modifier, 0.5-1.2 parts of an antioxidant, 0.5-1.5 parts of an ultraviolet absorber, and 1-2 parts of a lubricant; The inorganic modified body is diatomaceous earth surface-modified by a reactive flame retardant; The structure of the reactive flame retardant is shown below: ; The preparation method of the inorganic modified body is as follows: The acid-treated diatomaceous earth is mixed with toluene, and ultrasonically dispersed for 30-40 minutes at an ultrasonic frequency of 80-120 kHz, and then the reactive flame retardant is added to the formed dispersion, and the catalyst is added at the same time, and mechanical mixing is performed, and then the temperature is gradually controlled to 60-70°C, and after heat preservation for 3-6 hours, the heating is stopped, and the solid material collected by centrifugal separation is washed and vacuum dried to obtain an inorganic modified body; The acid treatment method of the diatomaceous earth is as follows: Place the diatomaceous earth in a tube furnace, calcine it at 450-500°C for 1-2h, take it out, cool it naturally, transfer it to dilute sulfuric acid, then control the temperature to 45-55°C, keep it warm for 1-3h under constant stirring, discharge it, wash it and dry it.
2. The cable composite material with halogen-free flame retardant functionality according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene.
3. The cable composite material with halogen-free flame retardant functionality according to claim 1, characterized in that: The preparation method of the reactive flame retardant is as follows: Add 4-isocyanobenzoyl chloride and acetone to a reactor filled with nitrogen, start stirring, and after mixing evenly, add the flame retardant FRC-6 to the reactor under ice bath conditions. After the addition is complete, remove the ice bath, and then add the acid binding agent to the reactor. After the addition is complete, stir at room temperature for 2-4 hours, evaporate to remove the solvent, collect the material, and the reactive flame retardant can be obtained.
4. The cable composite material with halogen-free flame retardant functionality according to claim 3, characterized in that: The molar ratio of the 4-isocyanobenzoyl chloride to the flame retardant FRC-6 is 1:
2.
5. The cable composite material with halogen-free flame retardant functionality according to claim 3, characterized in that: The acid binding agent is pyridine or triethylamine.
6. The cable composite material with halogen-free flame retardant functionality according to claim 1, characterized in that: The catalyst is at least one of dibutyltin diacetate, dibutyltin dilaurate, stannous octoate or dibutyltin didodecylsulfide.
7. The cable composite material with halogen-free flame retardant functionality according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 168 and antioxidant 1010, with a mass ratio of 0.2-0.3:1; the ultraviolet absorber is any one of UV-292, UV-571 or UV-P; and the lubricant is any one of polyethylene wax, zinc stearate or calcium stearate.
8. A method for preparing a cable composite material having halogen-free flame retardant functionality as claimed in claim 1, characterized in that: The following steps are involved: The first step is to weigh each raw material according to the weight and set aside; The second step is to add all the raw materials into the mixer, mechanically stir and mix them at a speed of 1000-1500r / min for 30-60min to form a uniform mixture, and then feed the mixture into the extruder through the feeding hopper, control the extrusion temperature to 240-280°C, the screw speed to 200-250r / min, perform the extrusion granulation process, and then pelletize to obtain the cable composite material.
Citation Information
Patent Citations
Halogen-free flame-retardant linear low density polyethylene(LLDPE) material
CN105504482A
Glass-fiber-reinforced polycarbonate resin composition
CN105051110A
Preparation method of flame-retardant anti-aging butyronitrile cable
CN118546443A